Mineralogy and character of the Liikavaara Östra Cu-(W-Au) deposit, northern Sweden. (2nd July 2020) - Warlo, Mathis; Wanhainen, Christina; Martinsson, Olof; Karlsson, Peter
ABSTRACT: The Liikavaara Östra Cu-(W-Au) deposit is situated close to the operating Aitik Cu-Au mine in northern Sweden. It is scheduled for production in 2023. Modern geological descriptions of the deposit are lacking though knowledge of geological and mineralogical details prior to operation is beneficial to avoid surprises. In this study, petrological, mineralogical and geochemical investigations of the wall rocks, host rock and mineralisation, and zircon U-Pb analysis of a footwall granodioritic intrusion were carried out. The mineralisation is hosted by quartz±tourmaline-calcite veins, calcite veins and aplite dykes that cross-cut biotite-amphibole schists and gneisses. The wall rocks to the ore are metavolcaniclastic rocks of basaltic to andesitic composition. A granodiorite intrusion occurs in the footwall. The mineralisation is mainly chalcopyrite, pyrrhotite and pyrite with some sphalerite, galena, scheelite, molybdenite and magnetite. It shows slight enrichments in Au, Ag and Bi. Gold and Ag occur as electrum and Ag also in hessite and an Ag-sulphide. The Bi mineralogy includes native Bi, Bi-tellurides and Bi-sulphides. These minerals are found as inclusions, along the borders of and in cracks in chalcopyrite, pyrite, pyrrhotite, sphalerite, molybdenite and quartz. The footwall granodiorite intrusion was dated at 1.87 Ga. It is suggested here to be the source for ore genesis based on its spatial relation to the mineralisation, as well as on high-salinity fluids and metal composition of the ore. The aplite dykes may have acted as pathways for the magmatic hydrothermal fluids that carried the metals from the intrusion to the host rock.